The Effectiveness of Demonstrative Instruction Integrated with Digital Media in Improving Learning Outcomes in Fiqh on Qurban and Aqiqah at MAN Kota Tegal - Khilmah Khilmah; Iis Arifudin; Ade Hidayat (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study examines the effectiveness of a demonstrative learning model integrated with digital media in improving students’ learning outcomes on fiqh topics of qurban and aqiqah at MAN Kota Tegal. Using a quantitative approach, the study employed a quasi-experimental two-group pretest–posttest design with 140 students, comprising a control group (n = 70) and an experimental group (n = 70), implemented over four sessions across two weeks. Descriptive results show that the control group increased from M = 58.39; SD = 6.60 (pretest) to M = 75.37; SD = 9.40 (posttest), while the experimental group increased from M = 56.63; SD = 6.56 to M = 75.06; SD = 10.78. Paired-samples t-tests indicate significant improvements in both groups (control: t = 19.09; p < .001; experimental: t = 16.49; p < .001). However, between-group comparisons reveal no statistically significant differences in posttest scores (p = .854) or gain scores (p = .314), although the experimental group’s mean gain (M = 18.43; SD = 9.35) was slightly higher than the control group’s (M = 16.99; SD = 7.45). ANCOVA (posttest as the dependent variable, pretest as a covariate) further confirms a non-significant group effect (b = −1.19; p = .409), while baseline performance significantly predicts posttest (b = 0.86; p < .001; R² = .311). These findings suggest that learning outcomes improved substantially in both groups, yet the added value of digital integration within the demonstrative model was not statistically superior to the comparison instruction under the observed context and duration.